2016
DOI: 10.1016/j.tjem.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Acute ischemic stroke and severe multiorgan dysfunction due to multiple bee stings

Abstract: Various manifestations after bee sting have been described. Local reactions, such as pain, wheal, flare, edema and swelling, are common and generally self-limiting. Uncommonly manifestations like vomiting, diarrhea, dyspnea, generalized edema, acute renal failure, anaphylactic shock, myocardial infarction, hypotension, collapse, pulmonary hemorrhage, acute hemorrhagic pancreatitis, and atrial fibrillation may occur. We report a 59 year-old man who sustained ischemic stroke and multi-organ dysfunction following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 13 publications
1
0
0
2
Order By: Relevance
“…Association between dopamine and new onset AF was reported before [3]. Previously reported that, kidney injury, acute ischemic stroke and multiorgan dysfunctions ensued from poisoning effects of the bee venom [1,4]. Heart blocks and myocardial infarctions have reported due to the bee sting but as in our case AF is a very rare complication of the bee sting [2].…”
Section: Discussionsupporting
confidence: 50%
“…Association between dopamine and new onset AF was reported before [3]. Previously reported that, kidney injury, acute ischemic stroke and multiorgan dysfunctions ensued from poisoning effects of the bee venom [1,4]. Heart blocks and myocardial infarctions have reported due to the bee sting but as in our case AF is a very rare complication of the bee sting [2].…”
Section: Discussionsupporting
confidence: 50%
“…İskemik inme, epileptik nöbet, optik nörit, fasial paralizi Guillain Barre sendromu, ensefalopati, akut dissemine ensefalomiyelit, plexopati, parkinsonizm olgu sunumları ile bildirilen nörolojik tutulumlar arasındadır. [5][6][7][8][9][10][11][12][13] Yaban arısı sokması sonrası jeneralize tonik klonik nöbet geçiren olgu, nöbetin arı sokmasının ender bir komplikasyonu olması nedeniyle sunuldu.…”
Section: Introductionunclassified
“…Kan laboratuvar incelemelerinde beyaz küre (WBC)=15,7 K/uL(3,(5)(6)(7)(8)(9)(10)5), hemoglobin=14,1 g/dL(13,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)5), trombosit=304 K/uL (150-450), B12=299,1 pg/mL (191-663), folik asit=10,76 ng/mL (3,1-17,5) bulundu. Kan şekeri=151 mg/dL (70-110), üre=42 mg/dL (18te belirlendi (Resim 1A, 1B).…”
unclassified